Consent and consultation under IPILRA and the MPRDA concerning ancestral land of customary communities: incorporating the free, prior, and informed consent principle into South African National Legislation - Maponya, Randy (Department of Private Law, 2025)
The Mineral and Petroleum Resources and Development Act 28 of 2002 (MPRDA) requires an applicant for a right to a mineral or a mining permit to consult with the landowner, lawful occupier, or any interested and affected parties. The MPRDA does not require the applicant for a right to a mineral or a mining permit to obtain consent, it only requires that the applicant consults with the landowner, lawful occupier, or any interested and affected parties. The Interim Protection of Informal Land Rights Act 31 of 1996 (IPILRA), requires the informal land rights holders consent to any deprivation of their informal rights to land. The court in Baleni v Minister of Mineral Resources (Baleni 1) considered the level of engagement that must be achieved before a right to a mineral or mining permit may be granted by the Minister in terms of the MPRDA. The court in Baleni confirmed that an informal land right holder must consent to any deprivation of their informal land right. The court held that the MPRDA and IPILRA must be read together. The court in Baleni 1 considered customary law and international law as prescribed in the Constitution of the Republic of South Africa of 1996 (Constitution). The court recognised international instruments under international and regional law that deal with the Free, Prior, and Informed Consent (FPIC) principle. Basson J held that requiring community consent as opposed to consultation is in line with the FPIC principle recognised under international law. This dissertation aims to examine whether the Baleni 1 judgment paves the way for the incorporation of the FPIC principle into South African national legislation. It investigates the challenges and benefits of incorporating the FPIC principle into national legislation and the implementation of the FPIC principle in practice. Further, the role of the legislature in adopting the FPIC principle into national legislation as opposed to adopting the requirement of consent. This dissertation argues that the Baleni 1 judgment paves the way for the FPIC principle to be incorporated into South African national legislation. The dissertation unpacks the FPIC principle as outlined in international law and how it can be applied in domestic law. This dissertation seeks to illustrate how the FPIC principle can be incorporated into national South African legislation for the protection of customary communities on ancestral land affected by prospecting and mining operations.